2009
DOI: 10.3986/ac.v38i2-3.123
|View full text |Cite
|
Sign up to set email alerts
|

Surface Versus Underground Measurements of Active Tectonic Displacements with TM 71 Exstensometers in Slovenia

Abstract: UDC 551.24(497.4-15) Andrej Gosar, Stanka Šebela, Blahoslav Košťák & Josef Stemberk: Surface versus underground measurements of active tectonic displacements with TM 71 exstensometers in Slovenia The tectonic setting of W Slovenia is characterised by NW-SE trending dextral strike-slip fault systems and moderate seismicity. Monitoring of tectonic movements along five presumably active faults or in their vicinity using TM 71 extensometers was set up in 2004. In five years of monitoring some clear trends of displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Postojna Cave has been under permanent radon survey since 1995, because of elevated radon concentrations (Kobal et al ., ; Vaupotič et al ., ; Vaupotič, ). More recently, air temperature and pressure monitoring has been conducted to better understand radon emanations connected with microtectonic displacements of two monitoring sites (Gosar et al ., ; Šebela et al ., ; Šebela and Turk, ). All these studies have brought to light the complexity of the Postojna Cave microclimate, influenced by numerous known and unknown entrances at different levels and the long and highly ramified cave system.…”
Section: Introductionmentioning
confidence: 99%
“…Postojna Cave has been under permanent radon survey since 1995, because of elevated radon concentrations (Kobal et al ., ; Vaupotič et al ., ; Vaupotič, ). More recently, air temperature and pressure monitoring has been conducted to better understand radon emanations connected with microtectonic displacements of two monitoring sites (Gosar et al ., ; Šebela et al ., ; Šebela and Turk, ). All these studies have brought to light the complexity of the Postojna Cave microclimate, influenced by numerous known and unknown entrances at different levels and the long and highly ramified cave system.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages and limitations of the instrument are well defined given the protracted installation at a number of sites in, for example, the Czech Re− public, Slovenia, Slovakia, and Poland (Kontny et al 2005;Gosar et al 2009;Šebela et al 2009). It has been shown that seasonal and climatic variations can be detected and separated from the recorded movements (Briestenský et al 2010).…”
Section: Fault Displacement Monitoringmentioning
confidence: 99%
“…The complexity and size of Postojna Cave, with its numerous known and unknown entrances at different levels and a long and highly ramified cave system, makes this cave a fascinating study site for a variety of physical and environmental studies (Bezek et al, 2012;Gosar et al, 2009;Kobal et al, 1988;Mulec et al, 2012;Šebela et al, 2010;Šebela and Turk, 2011;Vaupotič, 2008). In general the ventilation of Postojna Cave is characterised by convective airflow, controlled mainly by the temperature difference between the cave and the outside atmosphere, as discussed by for one measurement location in the Velika Gora (Great Mountain) chamber of Postojna Cave.…”
Section: Introductionmentioning
confidence: 99%